CAMPUR KODE DALAM KARANGAN SISWA KELAS VI SDN BALONGCABE KECAMATAN KEDUNGADEM KABUPATEN BOJONEGORO - Suparlan Suparlan (EDU-KATA, 2014)
The data of reseach were gathered from the students’ writing products from 6th graders of SDN Balongcabe, Kedungadem, Bojonegoro by using the instruments and agregation of data, data reduction, data display, and conclusion drawing/verification.The aim of study was to discribe the code-hybrid from the students elementary schools’ opus, development and usage errors. The data of research show presence code hybrid from the students’ writingproduct from 6th graders of SDN Balongcabe, Kedungadem, Bojonegoro. Code hybrid consist at the rank of sentence and word. Usage the language to code hybrid is Indonesian Language and Java language.